2020
DOI: 10.1111/jdv.16186
|View full text |Cite
|
Sign up to set email alerts
|

Trachyonychia: a retrospective study of 122 patients in a period of 30 years

Abstract: Background Trachyonychia is a nail disease characterized by longitudinal striations, ridges, fissures and/or pitting. This condition can be both idiopathic and associated with other dermatologic diseases. Objective and methods The aim of this retrospective study was to analyse the clinical features, onychoscopy, therapy efficacy and outcome of 122 patients with trachyonychia visited at the Hair Disease Outpatient Consultations of the Dermatology Unit of the Department of Experimental, Diagnostic and Specialty … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 12 publications
1
33
0
Order By: Relevance
“…Significantly lower percentages were seen with patients demonstrating the psoriasiform pattern (16.7%), lichenoid pattern (13.3%), and a non‐specific pattern (16.7%). These data support what has been shown in prior literature 2,3 : that the spongiotic pattern is by far the most prevalent histopathologic pattern identified in trachyonychia. The psoriasiform and lichenoid patterns have also been identified with trachyonychia in prior literature, with some degree of variability from what is reported in the study by Hur et al However, the data presented by Hur et al confirm that these other two histopathologic patterns occur with substantially lower frequency.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…Significantly lower percentages were seen with patients demonstrating the psoriasiform pattern (16.7%), lichenoid pattern (13.3%), and a non‐specific pattern (16.7%). These data support what has been shown in prior literature 2,3 : that the spongiotic pattern is by far the most prevalent histopathologic pattern identified in trachyonychia. The psoriasiform and lichenoid patterns have also been identified with trachyonychia in prior literature, with some degree of variability from what is reported in the study by Hur et al However, the data presented by Hur et al confirm that these other two histopathologic patterns occur with substantially lower frequency.…”
supporting
confidence: 92%
“…Trachyonychia is a non‐scarring process, and can spontaneously resolve or improve on its own (although this may take years), or with a variety of therapies 2‐4 . Thus, nail unit biopsies for this condition are generally disfavored because the potential risks of the procedure can outweigh the benefits.…”
mentioning
confidence: 99%
“…Recently, the same institution examined the nail matrix tissues of 29 trachyonychia cases, which is the largest pathological study to date 6,7 . They showed that 21 cases (72.4%) had spongiotic changes, 5 (17.2%) with psoriasiform pattern, and 3 (10.3%) with histopathologic features of the lichen planus 7 . Our histopathologic analysis data revealed lymphocytic infiltrates in the majority of cases (93.3%).…”
Section: Discussionmentioning
confidence: 72%
“…Inflammation severity affects both the subtype and number of involved nails. Starace et al reported that among 122 trachyonychia patients, opaque trachyonychia was detected in more severe cases with involvement of approximately 13.4 nails, while shiny trachyonychia was detected in milder cases with approximately 1.6 nails involved 7 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation